Interventions outside the workplace for reducing sedentary behaviour in adults under 60 - Murtagh, E; Murphy, M; Foster, C; Milton, K; Roberts, N; O'Gorman, C (Wiley, 2017)
This is a protocol for a Cochrane Review (Intervention). The objectives are as follows: To assess the effects of non-occupational interventions for reducing sedentary behaviour in adults under 60 years of age on sedentary time. Secondary objectives are: • to describe other health effects, and adverse events or unintended consequences of the interventions; • to determine whether specific components of interventions are associated with changes in sedentary behaviour; • to examine if there are any differential effects of interventions based on health inequalities (e.g. age, sex, income, employment).